Subjetividade transcendental: conceito epistemológico paradigmático na “Crítica da Razão Pura” - Carvalho, Francisco Nunes de (2021)
This research intends to approach an epistemological centrality of the concept of “Transcendental Subjectivity” having as main reference the work Critique of pure reason(Kritik der reinen Vernunft)of the philosopher Imannuel Kant. In this way, it proposes to examine the relevance of this theoretical-cognitive concept while constituting an epistemological paradigm, that is, as it divides a broad and exemplary theoretical model from which it allows to elucidate the human activity of constituting knowledge. And knowing is considered a human activity located and built within the expansive scope of possible experience, which requires circumscribing accessible and recognizable boundaries by exercising thefaculty of reason. This methodological approach of theoretical-bibliographic research is guided by the critical-transcendental theoretical perspective of knowledge. Such a critical-transcendental theoretical-cognitive examination is developed by considering universal and formative criteria of our human knowledge and in the way of realizing this knowledge, through reference to the theory of Subjectivity. The critical-transcendental theory of knowledge requires thematization of the human activity of knowledge brought back to its foundations by reflexivity on an epistemic unit that encompasses the cognitive-logical-propositional triad active in knowledge. This consideration of a transcendental theoretical examination is centered on cognitive intermediation from the capabilities, elements andacting of Subjectivity. Thus, making transcendental Philosophy consists of considering cognitive universality from a universality of Subjectivity.